2014
DOI: 10.1371/journal.pgen.1004464
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis DELLA Protein Degradation Is Controlled by a Type-One Protein Phosphatase, TOPP4

Abstract: Gibberellins (GAs) are a class of important phytohormones regulating a variety of physiological processes during normal plant growth and development. One of the major events during GA-mediated growth is the degradation of DELLA proteins, key negative regulators of GA signaling pathway. The stability of DELLA proteins is thought to be controlled by protein phosphorylation and dephosphorylation. Up to date, no phosphatase involved in this process has been identified. We have identified a dwarfed dominant-negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
107
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(111 citation statements)
references
References 74 publications
3
107
0
1
Order By: Relevance
“…In addition, two transfer DNA insertion lines of TOPP4, SALK_090980, and N466328 did not show any obvious PC defects (Qin et al, 2014;Supplemental Fig. S6), possibly due to the high expression level of TOPP4 in these two lines or functional redundancy among TOPP genes.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…In addition, two transfer DNA insertion lines of TOPP4, SALK_090980, and N466328 did not show any obvious PC defects (Qin et al, 2014;Supplemental Fig. S6), possibly due to the high expression level of TOPP4 in these two lines or functional redundancy among TOPP genes.…”
Section: Resultsmentioning
confidence: 97%
“…In our previous work, we identified a severely dwarfed dominant-negative mutant topp4-1 and found that TOPP4 acts as a positive regulator in GA signaling through dephosphorylating DELLA proteins (Qin et al, 2014). The topp4-1 mutant was also found to show PC defects.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Plants and animals use small molecules for inter-cellular signaling that are transduced by binding to disorder-containing receptor proteins, and PONDR VSL2b [45] and other disorder predictors indicate that the various plant homeodomain-containing transcription factors contain significant amounts of disorder, and they undergo PTM [46]. For example, rice KNOX undergoes tissue-specific AS [47], whereas DELLA proteins are phosphorylated for degradation [48].…”
Section: Discussionmentioning
confidence: 99%